Anesthesia in Low Ejection Fraction Patient : Case Report - Gemawan, Taufiq; Handoko, Adelia; Misturiansyah, Nurrul Izza (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2023)
Ejection fraction (EF) is the percentage of the difference between the end-diastolic volume and the end-systolic volume divided by the end-diastolic volume. This measurement is important in determining how well the heart is pumping out blood and in diagnosing heart failure (HF). Normally the percentage of EF is above 50%. A decrease in EF will make it difficult to perform anesthesia during surgery due to life-threatening irregular heartbeats, leading to sudden cardiac arrest and sudden death. Patients with a very low ejection fraction require identification of risk factors, preoperative evaluation and optimization, medical therapy, monitoring, and appropriate anesthetic technique and drugs. In this report, we present a 67-year-old woman with HFmrEF (estimated ejection fraction 46%) and coronary artery disease who underwent partial hip replacement surgery under general anesthesia. General anesthesia was performed on the patient and induction used fentanyl, midazolam, and atracurium. Management of patients is aimed at maintaining cardiac output and avoiding myocardial depression by maintaining a balance between oxygen supply and demand. Therefore good anesthetic management is needed to maintain the hemodynamic stability of the patient.